2016
DOI: 10.1063/1.4953220
|View full text |Cite
|
Sign up to set email alerts
|

Electromodulation spectroscopy of direct optical transitions in Ge1−xSnx layers under hydrostatic pressure and built-in strain

Abstract: Unstrained Ge1−xSnx layers of various Sn concentration (1.5%, 3%, 6% Sn) and Ge0.97Sn0.03 layers with built-in compressive (ε = −0.5%) and tensile (ε = 0.3%) strain are grown by molecular beam epitaxy and studied by electromodulation spectroscopy (i.e., contactless electroreflectance and photoreflectance (PR)). In order to obtain unstrained GeSn layers and layers with different built-in in-plane strains, virtual InGaAs substrates of different compositions are grown prior to the deposition of GeSn layers. For u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Moreover such approach is more safe in this case taking into account the narrow bandgap of GeSn and quite large range of bowing parameters reported in the literature for this alloy. Additionally, it has been shown that the Bir-Pikus theory 49 can be applied to description of the strain-related shifts in the conduction and valence bands in this alloy 28 50 . This theory has been used by us to calculate the quantum confinement potential for electrons and holes in strained GeSn/Ge QWs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover such approach is more safe in this case taking into account the narrow bandgap of GeSn and quite large range of bowing parameters reported in the literature for this alloy. Additionally, it has been shown that the Bir-Pikus theory 49 can be applied to description of the strain-related shifts in the conduction and valence bands in this alloy 28 50 . This theory has been used by us to calculate the quantum confinement potential for electrons and holes in strained GeSn/Ge QWs.…”
Section: Resultsmentioning
confidence: 99%
“…In this case the strain-related shifts for CB, HH, LH, and SO band are calculated using the Bir-Pikus theory 72 , see proper formulas in the Methods section. So far it has been shown that this theory works very well in this material system in the range of low built-in strains 15,73 , i.e., the range which is considered in this work.
Figure 3Conduction (Γ and L point) and the valence (HH, LH, and SO) band maxima for Ga 1−w Sn w QW material strained on virtual Ga 1-z Sn z substrate with z = 0.05, 0.10, and 0.15. Dashed lines show the conduction and valence band position for Si y Ge 1−x−y Sn x barrier lattice matched to the virtual substrate.
…”
Section: Materials Selectionmentioning
confidence: 88%
“…The room-temperature electron mobility increases from 140 cm 2 /Vs in GeSnP1 to 175 cm 2 /Vs in GeSnP3. Since the Sn concentration is the same in all samples, the enhancement of the carrier mobility and the change of the band gap can be associated with the strain engineering and the band gap renormalization, respectively [46,47]. Figure 6b shows the values for the direct band gap  in bulk Ge, tensile stained Ge-on-Si, undoped GeSn and very heavily doped GeSn alloys.…”
Section: Experimental Datamentioning
confidence: 99%